Oestrus induction using insulin modified Co-synch protocol in postpartum anoestrus cows - George Mathew; C.P. Abdul Azeez; K. Promod; Leeba Chacko; Renjith Sebastian (Journal of Veterinary and Animal Sciences, 2025)
Efficacy of Co-synch and insulin modified Co-synch protocols for the treatment of post-partum anoestrus crossbred cows were studied. True anoestrus was confirmed by per-rectal examination conducted on day 50 and 60 (day 0) post-partum. Twenty-four cows were selected and divided in to two treatment and one control groups (n8). Group I cows were treated with Co-synch protocol; group II (Insulin modified Cosynch protocol) cows in addition to Co-synch, insulin (0.2 IUkg as SC) was also administered for three days on day 0, 1 and 2. Group III cows were the control group. Response to oestrus induction, time taken for the onset, duration and intensity of oestrus, physical changes in the reproductive tract and pregnancy rates were evaluated between the groups. Serum progesterone and insulin like growth factor-1(IGF-1) levels were estimated. Response to oestrus induction was 75 and 87.50 per cent for group I and II, respectively. Mean time taken for the onset and duration of oestrus were 41.41 1.47 and 14.41 0.43 h; 40.57 2.09 and 18.92 3.69 h for group I and II, respectively and for group III, only two cows showed oestrus on 68 and 76 day post-partum with average duration of 17.25 h. Significantly higher concentration of progesterone was observed in Group-I and Group-II than Group III cows on day 7 of treatment and day 10 post AI. Serum concentration of IGF-1 on day 7 and 9 of treatment and on day 10 post AI in group II was significantly higher (p